Achieving high strength and ductility in graphene/magnesium composite via an in-situ reaction wetting process. (November 2018) - Wang, Miao; Zhao, Yu; Wang, Li-Dong; Zhu, Yun-Peng; Wang, Xiao-Jun; Sheng, Jie; Yang, Zi-Yue; Shi, Hai-Long; Shi, Zhen-Dong; Fei, Wei-Dong
Abstract: The dispersibility and interfacial wettability are two essential requirements for fabricating graphene/metal composites with high performance. However, the simultaneous improvement of dispersibility and wettability between the graphene and metal matrix is still a challenge. Herein we attempted to improve the dispersibility, interfacial wettability and mechanical properties of graphene/magnesium composites via an in-situ reaction wetting process. Graphene oxide (GO) was modified with ZnO coating by a coprecipitation route, and the composites were fabricated by an ultrasonic assisted stir casting method. The composites showed a microstructure with homogeneous dispersion of graphene in the matrix. Compared with unreinforced Mg matrix, the composites demonstrated an exceptional and joint improvement in yield strength, hardness, and good ductility. Microstructural examinations revealed that the molten Mg could react with ZnO coating and form an interfacial product composed of MgO during the composite fabrication. The interfacial in-situ reaction could facilitate interfacial wetting and the interfacial product MgO could improve the interfacial bonding between graphene and matrix. The grain-size refinement and load transfer provided by graphene were the two main strengthening mechanisms in the composite. This study provides new insights into the interfacial design of advanced graphene/metal composites with exceptionally high strength and ductility. Graphical abstract: Image 1